Management of information security - Whitman, Michael E., 1964-; Mattord, Herbert J. (Boston, Mass. : Thomson Course Technology, 2008)
Management of Information Security, International Edition focuses on the managerial aspects of information security and assurance. Topics covered include access control models, information security governance, and information security program assessment and metrics. Coverage on the foundational and technical components of information security is included to reinforce key concepts. This new edition includes up-to-date information on changes in the field such as revised sections on national and international laws and international standards like the ISO 27000 series. With these updates, Management of Information Security continues to offer a unique overview of information security from a management perspective while maintaining a finger on the pulse of industry changes and academic relevance.
ch. 1. Introduction to the management of information security -- ch. 2. Planning for security -- ch. 3. Planning for contingencies -- ch. 4. Information security policy -- ch. 5. Developing the security program -- ch. 6. Security management models and practices -- ch. 7. Risk management -- ch. 8. Risk management -- ch. 9. Protection mechanisms -- ch. 10. Personnel and security -- ch. 11. Law and ethics -- ch. 12. Information security project management.
Includes bibliographical references and index.
1
Keywords: Computer networks -- Security measures; Computer security; Management information systems -- Security measures